2022
DOI: 10.1186/s40164-022-00298-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of m6A writers, erasers and readers in cancer

Abstract: The N(6)-methyladenosine (m6A) modification is the most pervasive modification of human RNAs. In recent years, an increasing number of studies have suggested that m6A likely plays important roles in cancers. Many studies have demonstrated that m6A is involved in the biological functions of cancer cells, such as proliferation, invasion, metastasis, and drug resistance. In addition, m6A is closely related to the prognosis of cancer patients. In this review, we highlight recent advances in understanding the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 318 publications
0
55
0
Order By: Relevance
“…RNA modification is an essential post-transcriptional mechanism that rapidly mediates RNA and protein levels without affecting DNA or histones. The regulation and function of the RNA methylation m 6 A in human malignancies have been studied most intensively, revealing that m 6 A affects various tumor processes [ 36 , 37 ], such as proliferation [ 20 , 21 ], stemness [ 38 ], and metastasis formation [ 39 ]. Besides, m 5 C mediates mRNA stability and translation, exerting powerful effects in multiple tumor types [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA modification is an essential post-transcriptional mechanism that rapidly mediates RNA and protein levels without affecting DNA or histones. The regulation and function of the RNA methylation m 6 A in human malignancies have been studied most intensively, revealing that m 6 A affects various tumor processes [ 36 , 37 ], such as proliferation [ 20 , 21 ], stemness [ 38 ], and metastasis formation [ 39 ]. Besides, m 5 C mediates mRNA stability and translation, exerting powerful effects in multiple tumor types [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the potential significance of RNA m 6 A modification in human health and disease, efforts of the past few years have focused on the identification of regulators of this modification. m 6 A methylation is introduced by methyltransferases and can be removed either passively, via the degradation of the modified RNA, or actively, by erasers such as the dioxygenases FTO or ALKBH5 [ 7 , 17 , 18 , 19 ]. Resembling the function ascribed to histone modifications, m 6 A modification can cause a structural switch and/or act as a signal for the recruitment of downstream effectors that influence the fate of the target mRNA [ 20 , 21 , 22 , 23 , 24 ].…”
Section: M 6 a Rna Methylationmentioning
confidence: 99%
“…Some readers, such as YTH-domain-containing family members, can bind directly to m 6 A methylated RNAs. Alternatively, the modulation of the secondary RNA structure can expose or mask RNA-binding motifs recognized by reader proteins, leading to an m 6 A-dependent regulation of RNA maturation and gene expression [ 7 , 17 , 18 , 19 ].…”
Section: M 6 a Rna Methylationmentioning
confidence: 99%
“…It suggested that the m 6 A modi cation might also play a crucial regulatory role in the development and progression of human cancers. Along with the in-depth study, 23 regulatory genes related to m 6 A modi cation were known (8 Writers, 13 Readers and 2 Erasers) were identi ed thoroughly [9,10]. More and more studies have demonstrated that these 23 m 6 A regulators closely participated in the cancer progression.…”
Section: Introductionmentioning
confidence: 99%